Registration of 'WB3768' Wheat. Issue 3 (1st August 2014) - Berg, J. E.; Wichman, D. M.; Kephart, K. D.; Eckhoff, J. L.; Stougaard, R. N.; Lamb, P. F.; Miller, J. H.; Nash, D. L.; Grey, W. E.; Johnston, M.; Gettel, D.; Larson, R.; et al.
Abstract : 'WB3768' (Reg. No. CV‐1100, PI 670158) hard white winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in September 2013. An exclusive license for commercialization of WB3768 was granted to Monsanto. WB3768 is of unknown pedigree, derived from a composite of two related topcrosses: MTW0047 ('Judith'/PI 262605//S86‐740)/2*MT9982 and MTW0047/MT9982//MT9989 (Judith/'Arapahoe'). MT9982 is a sib selection of 'Yellowstone', and S86‐740 ('Norstar'/''Plainsman V'//'Ulianovkia') is an unreleased breeding line developed by the Crop Development Center in Saskatoon, Saskatchewan. WB3768 was developed using a modified bulk breeding method and selected as an F5:6 headrow. WB3768 was tested under the experimental number MTW08168 in Montana yield trials from 2009 to 2013. WB3768 is a high‐yielding, winter‐hardy, conventional‐height hard white winter wheat line with late maturity, medium to high grain protein, low polyphenol oxidase activity, and acceptable milling and baking quality. WB3768 was released for its combination of the hard white market class and excellent yield performance in winter wheat production environments of Montana.